2020
DOI: 10.1111/2041-210x.13378
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐species occupancy models as robust estimators of community richness

Abstract: 1. Understanding patterns of diversity is central to ecology and conservation, yet estimates of diversity are often biased by imperfect detection. In recent years, multi-species occupancy models (MSOM) have been developed as a statistical tool to account for species-specific heterogeneity in detection while estimating true measures of diversity. Although the power of these models has been tested in various ways, their ability to estimate gamma diversity-or true community size, N is a largely unrecognized featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 35 publications
0
26
2
Order By: Relevance
“…Given the considerable attention paid to the mammals of the study region, we are confident that actual richness is known (13 species), in agreement with atlas cumulative data [ 37 ]. Species richness calculated with the non-parametric index iChao2 clearly overestimated true richness in contrast with recent analyses indicating that iChao2 tends to underestimate richness both in virtual and real communities with a larger number of species (20–125 species; [ 59 ]). Although Tingley et al [ 59 ] concluded that iChao2 was an accurate estimator, they also showed that accuracy notably decreases when mean species probability of occupancy is low (0.1) and highly variable (SD = 1.0), regardless of variation in the average species probability of detection.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Given the considerable attention paid to the mammals of the study region, we are confident that actual richness is known (13 species), in agreement with atlas cumulative data [ 37 ]. Species richness calculated with the non-parametric index iChao2 clearly overestimated true richness in contrast with recent analyses indicating that iChao2 tends to underestimate richness both in virtual and real communities with a larger number of species (20–125 species; [ 59 ]). Although Tingley et al [ 59 ] concluded that iChao2 was an accurate estimator, they also showed that accuracy notably decreases when mean species probability of occupancy is low (0.1) and highly variable (SD = 1.0), regardless of variation in the average species probability of detection.…”
Section: Discussioncontrasting
confidence: 79%
“…Species richness calculated with the non-parametric index iChao2 clearly overestimated true richness in contrast with recent analyses indicating that iChao2 tends to underestimate richness both in virtual and real communities with a larger number of species (20–125 species; [ 59 ]). Although Tingley et al [ 59 ] concluded that iChao2 was an accurate estimator, they also showed that accuracy notably decreases when mean species probability of occupancy is low (0.1) and highly variable (SD = 1.0), regardless of variation in the average species probability of detection. However, we found considerable overestimation of species richness even with high probabilities of occupancy (mean ± SD = 0.77 ± 0.37; n = 13 species) which are closer to scenarios where iChao2 performed better [ 59 ].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…While we were able to detect the majority of species predicted to be present on St. Kitts, our actual ability to detect a given mosquito species was low on average (9% average detection rate). That being said, multi-species occupancy models are robust to low detection probabilities as long as mean site-level occupancy is relatively high, which it was in this study (30%) [ 44 ]. Using the site-level species richness estimated from our multi-species occupancy model, we noted some potential correlation between percentage of local land cover and mosquito species richness.…”
Section: Discussionmentioning
confidence: 79%